The Subjective Meaning and Means of Happiness: Lessons Learned from Qaryah Thayyibah Program - Rofiqah Rofiqah; Zainul Arifin (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
Qaryah Thayyibah, which is part of the Maulana Malik Ibrahim State Islamic University program, is in line with the series of baldatun thayyibah expressions, which should be a kind of ideal image tiered from village, city to country. Residents of villages, cities or countries, and especially the Government, also according to Islamic teachings, are obliged to prioritize those who are left behind, to be the first to receive assistance (putting the last first). Qaryah Thayyibah, a team of lecturers and students at the State Islamic University of Maulana Malik Ibrahim Malang, aims to accompany and strengthen movement towards goodness and progress in accordance with their potential and competence. The approach used, participatory community education and development (Community Participatory Education and Development) and type of institutional program. From the activities and self-evaluation of Qaryah Thayyibah participants, a Brief Subjective Scale of Happiness was compiled which contains ten indicators and questions about factors of happiness and well-being, both instrumental and terminal. Based on exploratory and confirmatory factor analysis, it is known that there are three factorial components of people's subjective happiness, namely: the trust factor in disaster, the gratitude factor in grace, and the trust factor in the congregation. Using a sequential exploratory mixed study approach (sequential exploratory mix method), data is being collected in the context of research into the development of the Community's Brief Subjective Happiness Inventory, and the Predictive Validity of Community's Brief Subjective Happiness on Community Objective Welfare, which relies on the results of observations and calculations of fulfilling material-physical needs . It is highly recommended to prioritize community development and development of rural-urban transitional areas, such as Kedungkandang District, not only for the sake of social justice, but also for the future of the city.